The Impact of Commodity Price Changes on Rural Households : The Case of Coffee in Uganda - Bussolo, Maurizio; Godart, Olivier; Lay, Jann; Thiele, Rainer (World Bank, Washington, DC, 2012)
Policies and external shocks affecting agriculture, the main source of income for rural households, can be expected to have a significant impact on poverty. The authors study the case of Uganda. Throughout the 1990s, more than 90 percent of its poor lived in rural areas and, during the same period, large international price fluctuations as well as an extensive domestic deregulation affected the coffee sector, its main source of export revenues. Using data from three household surveys covering the 1990s, the authors confirm a strong correlation between changes in coffee prices (in a liberalized market) and poverty reduction. This is highlighted by comparing the performance of different households grouped according to their dependence on coffee farming. Regression analysis (based on pooled data from the three surveys) of consumption expenditure on coffee-related variables, other controls, and time-fixed effects corroborates that the mentioned correlation is not spurious. The authors also find that while both poor and rich farmers enter the coffee sector, the price boom benefits the poorer households relatively more, whereas the liberalization seems to create more opportunities for richer farmers. Finally, notwithstanding the importance of the coffee price boom, the agricultural policy framework and the thorough structural reforms in which the coffee market liberalization was embedded have certainly played a role in triggering overall agricultural growth. These factors appear to matter especially in the second half of the 1990s when prices went down but poverty reduction continued.